2015
DOI: 10.1111/jmwh.12329
|View full text |Cite|
|
Sign up to set email alerts
|

Midwives in Medical Student and Resident Education and the Development of the Medical Education Caucus Toolkit

Abstract: Midwives have been involved formally and informally in the training of medical students and residents for many years. Recent reductions in resident work hours, emphasis on collaborative practice, and a focus on midwives as key members of the maternity care model have increased the involvement of midwives in medical education. Midwives work in academic settings as educators to teach the midwifery model of care, collaboration, teamwork, and professionalism to medical students and residents. In 2009, members of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Integrated teaching between different teams has proven beneficial. There is recognition of the value the teacher brings and reports of positive clinical learning experiences [10]. In joint psychological and obstetric teaching ward rounds for medical students integrated session reported students being better prepared for the psycho-social aspects of obstetrics [11].…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated teaching between different teams has proven beneficial. There is recognition of the value the teacher brings and reports of positive clinical learning experiences [10]. In joint psychological and obstetric teaching ward rounds for medical students integrated session reported students being better prepared for the psycho-social aspects of obstetrics [11].…”
Section: Main Findingsmentioning
confidence: 99%
“…Many midwives (>97%) who teach have more than five years clinical experience, with nearly three quarters having more than five years experience teaching medical and midwifery students [12]. It is acknowledged that many academic practices are moving towards collaborative interdisciplinary teaching models [10]. At present midwives can teach medical students but there are no national standards or expectations.…”
Section: Main Findingsmentioning
confidence: 99%
“…ACOG and ACNM agree there is a need for more of both types of perintal care providers . Midwives teach in many residency programs . Testing IPE models at these locations first is one way to examine opportunities to expand educational opportunities for midwifery students.…”
Section: Enhancing the Perinatal Care Workforcementioning
confidence: 99%
“…17 Midwifery involvement in resident education has been well documented and associated with positive outcomes. 18 Given the higher rates of breastfeeding initiation and duration of patients receiving midwifery care and the posi- tive outcomes of midwifery-led residency education, midwives are well poised to spearhead breastfeeding education as part of an interprofessional model. Ogburn et al reported on a breastfeeding medicine curriculum developed by a multidisciplinary team of pediatricians, obstetrician-gynecologists, family health care providers, and one midwife.…”
Section: Midwives and Breastfeedingmentioning
confidence: 99%
“…Midwifery involvement in resident education has been well documented and associated with positive outcomes . Given the higher rates of breastfeeding initiation and duration of patients receiving midwifery care and the positive outcomes of midwifery‐led residency education, midwives are well poised to spearhead breastfeeding education as part of an interprofessional model.…”
Section: Introductionmentioning
confidence: 99%